2002
DOI: 10.1034/j.1600-0722.2002.21320.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stressful situations, salivary flow rate and oral volatile sulfur‐containing compounds

Abstract: The relationship between stress, salivary flow rate and oral volatile sulfur-containing compounds (VSCs) is not clearly established. Two stressful situations were studied: psychological stress caused by a biochemistry examination (Study I) and psychophysiological stress caused by premenstrual syndrome (PMS) (Study II). Seventy-one undergraduate dental students took part in Study I and VSCs were measured 1 wk before the examination, on the day of examination and 1 wk after. In Study II, 50 women were selected (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
3
29

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 30 publications
5
63
3
29
Order By: Relevance
“…2. We surmise that baseline salivation may be suppressed by stress before and during training (Queiroz et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2. We surmise that baseline salivation may be suppressed by stress before and during training (Queiroz et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…45 One such cause is the anaerobic production of volatile sulphur compounds by bacteria in the mouth, and in stress there is an increased concentration of sulphur compounds in saliva. 31 However, not all persons with subjective halitosis have significant malodour and this may have a psychogenic basis or be attributable to a form of delusion or monosymptomatic hypochondriasis, 45 or organic disease including cerebral tumour. Within the BMS patient group, subjective halitosis is also a common finding 2 and the objective assessment of this symptom is an important parameter in the workup.…”
Section: Other Sensory Complaintsmentioning
confidence: 99%
“…Investigations of the stress response associated with particular situations including examinations and fear of pain show reduced flow rates, decreased pH values, and increased protein and amylase concentrations. 31 Psychological and physiological stress exacerbated by examinations or menstruation can also cause an increase in oral volatile sulphurcontaining compounds 31 and variation in total ion concentration. Numerous studies have confirmed the relationship between anxiety, stress and particularly depression with a lowering of unstimulated salivary flow rates, 32 and most readers will relate to both acute onset oral dryness in situations such as unexpected public exposure or to slower onset in situations such as the lead-up to a planned public exposure, e.g., giving a speech.…”
Section: Xerostomia and Sialorrhoeamentioning
confidence: 99%
See 1 more Smart Citation
“…스 트레스는 신경계, 내분비계, 면역계 등의 신체기능에 생 리적인 변화 [2]를 일으킬 수 있을 뿐만 아니라 구강 질환 및 구취에 영향을 줄 수 있다 [3,4]. 스트레스 인자에 의해 신체가 저항력을 높이기 위해 각종 호르몬을 분비하게 되는데 이러한 반응들이 변화하게 되면 많은 질병을 일 으킨다고 보고 있다 [5].…”
Section: 서론unclassified